2009
DOI: 10.1007/s12192-008-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

RDJ2 (DNAJA2) chaperones neural G protein signaling pathways

Abstract: A number of structurally divergent proteins with J domains, called J proteins, interact with and activate the ATPase of Hsp70s, thereby harnessing the ATPase activity for conformational work on target proteins. The precise role of most mammalian J proteins remains undefined. In this paper, we demonstrate that transient expression of the J protein, Rdj2, in HEK 293 cells increased cellular cyclic adenosine monophosphate (cAMP) levels in the presence of the β-adrenergic agonist isoproterenol. In CNS-derived cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Furthermore, knockdown of DJA1 reduced the clearance of misfolded mutant cystic fibrosis transmembrane regulator from the cell surface, and DJA2 knockdown did not (41). In contrast, DJA2 has been identified as an enhancer of G-protein-coupled signaling by the ␤2-adrenergic receptor (42). Although functions of DJA2 and DJA1 independent of Hsc70 are possible, it is generally thought that their main roles are as co-chaperones of Hsc70.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knockdown of DJA1 reduced the clearance of misfolded mutant cystic fibrosis transmembrane regulator from the cell surface, and DJA2 knockdown did not (41). In contrast, DJA2 has been identified as an enhancer of G-protein-coupled signaling by the ␤2-adrenergic receptor (42). Although functions of DJA2 and DJA1 independent of Hsc70 are possible, it is generally thought that their main roles are as co-chaperones of Hsc70.…”
Section: Discussionmentioning
confidence: 99%
“…Also both Hsp70 proteins and DnaJ proteins have been shown to directly interact with GPCRs modulating their processing, whilst CSP binds G protein subunits. Furthermore, another DnaJ protein, Rdj2 (DnaJA2), has recently been shown to interact with G proteins and can modulate G protein signalling (Rosales-Hernandez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To date, we have a very limited understanding of this subclass A DNAJ protein. Localization studies have indicated that DNAJA2/Rdj2 is a neuroprotein expressed in all cell types of the whole rodent brain (Rosales-Hernandez et al , 2009). Moreover, DNAJA2/Rdj2 has been reported to be part of the multimeric chaperone complex with HSPA, HSPH, HSPC, HSP-interacting protein (Hip) and HSP organizing protein (Hop) (Craig et al , 2006).…”
Section: Hsp Family Catagorization: Untangling the Family Treementioning
confidence: 99%
“…Moreover, DNAJA2/Rdj2 has been reported to be part of the multimeric chaperone complex with HSPA, HSPH, HSPC, HSP-interacting protein (Hip) and HSP organizing protein (Hop) (Craig et al , 2006). In addition, DNAJA2/Rdj2 has been shown to associate with Gα and Gβ, which suggests that it is involved in G-protein signaling (Rosales-Hernandez et al , 2009). Ongoing efforts are underway to identify the specific G-protein signaling pathways and other functions of DNAJA2/Rdj2.…”
Section: Hsp Family Catagorization: Untangling the Family Treementioning
confidence: 99%